Price discovery : evidence from stock cross-listed on NASDAQ and SGX - Ang, Chiew Peng (2008)
This study investigates the price discovery process between NASDAQ and SGX, attempting to establish the non-existence of a dominant-satellite relationship between both markets. This justifies the decision of Creative Technology Ltd to delist from NASDAQ. In addition, availability of arbitrage opportunities is investigated to ascertain the level of market integration.